Peran Guru Pendidikan Agama Islam dalam Upaya Pembentukan Karakter Islami pada Peserta Didik pada Program BAMALAM di Sekolah Alam Minangkabau Kota Padang - Efendi, Yoki; Alfurqan, Alfurqan (ALSYS, 2025)
This research discusses the role of Islamic Religious Education (PAI) teachers in shaping students' Islamic character through the BAMALAM Program at Sekolahalam Minangkabau in Padang City. In a digital era full of moral and social challenges, character education is an urgent need for students. This study uses a qualitative approach with a case study method to understand the role of Islamic Religious Education (PAI) teachers in internalizing Islamic values through nature-based camping activities. Data were collected through interviews, observations, and documentation by involving teachers, principals, and students as participants. The results showed that Islamic Religious Education (PAI) teachers have a strategic role in shaping religious, independent, tolerance, cooperation, discipline, responsibility, and environmental care characters in students. This character building is realized through activities such as congregational prayer, tadarus Al-Qur'an, spiritual reflection, independent cooking, nature exploration, and the practice of caring for the environment. Although there are challenges such as the diversity of student characters and time constraints, Islamic Religious Education (PAI) teachers are able to overcome them with an inspirational and exemplary-based approach. In conclusion, the BAMALAM Program is an effective tool in building students' Islamic character, where the role of Islamic Religious Education (PAI) teachers as spiritual companions, motivators, and facilitators greatly contributes to the success of this program in forming a noble and responsible generation.